2020
DOI: 10.3390/md18120620
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation and Functional Studies of a Novel β-hairpin Antimicrobial Peptide from the Marine Polychaeta Capitella teleta

Abstract: Endogenous antimicrobial peptides (AMPs) are evolutionary ancient molecular factors of innate immunity that play a key role in host defense. Among the most active and stable under physiological conditions AMPs are the peptides of animal origin that adopt a β-hairpin conformation stabilized by disulfide bridges. In this study, a novel BRICHOS-domain related AMP from the marine polychaeta Capitella teleta, named capitellacin, was produced as the recombinant analogue and investigated. The mature capitellacin exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…The most recent of these is a 20 residue peptide, capitellacin (1), initially predicted (in 2014) from the genomic data of Capitella teleta, aided by a Basic Local Alignment Search (BLAST) of the genome sequence, based on the similarity of its BRICHOS domain and pro-region to previously isolated marine polychaetes AMPs (Panteleev et al 2018;Tasiemski et al 2014). More recently, Panteleev et al (2020) produced capitellacin (1) recombinantly in Escherichia coli and performed a thorough elucidation of its structure and activity (Panteleev et al 2020). Nuclear magnetic resonance (NMR) studies revealed capitellacin (1) to exist as a monomeric antiparallel β-hairpin (type IV β-turn) structure in solution, stabilised by two parallel disulfide bonds, showing significant sequence homology to the extensively studied and potent β-hairpin AMP, tachyplesin I (2) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent of these is a 20 residue peptide, capitellacin (1), initially predicted (in 2014) from the genomic data of Capitella teleta, aided by a Basic Local Alignment Search (BLAST) of the genome sequence, based on the similarity of its BRICHOS domain and pro-region to previously isolated marine polychaetes AMPs (Panteleev et al 2018;Tasiemski et al 2014). More recently, Panteleev et al (2020) produced capitellacin (1) recombinantly in Escherichia coli and performed a thorough elucidation of its structure and activity (Panteleev et al 2020). Nuclear magnetic resonance (NMR) studies revealed capitellacin (1) to exist as a monomeric antiparallel β-hairpin (type IV β-turn) structure in solution, stabilised by two parallel disulfide bonds, showing significant sequence homology to the extensively studied and potent β-hairpin AMP, tachyplesin I (2) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the antimicrobial activity of capitellacin demonstrated that this peptide has broad-spectrum activity, but it was up to eightfold lower than that of tachyplesin-1 (a peptide from the tachyplesins family). Unlike other peptides with β-hairpin structure, capithelinacin was inefficient in breaking the cytoplasmic membrane and inhibiting bacterial translation, suggesting other mechanisms of action and targets (Panteleev et al, 2020).…”
Section: Annelida Peptidesmentioning
confidence: 96%
“…Papers included in this Special Issue deal with marine polychaeta, providing good examples of their biological potential. The peptides arenicins and capitellacin, were isolated from Arenicola marina [ 16 ] and Capitella teleta [ 17 ], respectively. Earlier, structure-function relationships of arenicins have been extensively investigated [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
mentioning
confidence: 99%
“…Besides, this approach promotes antimicrobial effects, taking into account the inhibited complement system [ 26 ]. In this Special Issue, a novel BRICHOS-domain related AMP from the marine polychaeta Capitella teleta , named capitellacin, was reported [ 17 ]. The peptide exhibits high homology with β-hairpin marine peptides tachyplesins and polyphemusins from the horseshoe crabs.…”
mentioning
confidence: 99%
See 1 more Smart Citation